PHONOLOGICAL STRUCTURE OF SYLLABLES IN ENGLISH LEXICAL ITEMS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the syllabic structure of English words, detailing how syllables are organized and how they influence pronunciation, rhythm, and spelling. It explains the basic components of syllables—onset, nucleus, and coda—and categorizes different types of syllables such as open, closed, and vowel-consonant-e syllables. The article also touches on the process of syllabification, stress patterns, and their significance in language acquisition and communication. Emphasizing the role of syllabic structure in both native and non-native language learning, it underscores how understanding syllables aids in mastering pronunciation, reading, and writing in English. The article concludes by reflecting on the importance of syllables in understanding the complexity of English, providing insights into how language learners can improve their fluency and comprehension.